An analysis of Acehnese archaic words among North Acehnese speakers - Nanda Desriawati (Universitas Syiah Kuala, 2021)
This study concerned about the Acehnese archaic words in Lhokseumawe. The aims were to find out the archaic words, their replacements and their extinction factors. The researcher used qualitative descriptive methods and analyzed using three interactive models; data reduction, data display and verification. The result of this study showed that they are sixty Acehnese words given by informants; 32 words referred to archaism and 25 words referred to semi-archaism, and 3 words referred to non-archaism. 12 of 32 archaic words were replaced and 20 others were not. This condition was caused by the word-borrowing factors from second and foreign languages and also the lifestyle. Therefore, we need to teach Acehnese language to the future generation and introduce the Acehnese archaic words to especially the Acehnese in Lhokseumawe by studying and documenting the language and the archaic words as the language is a part of local cultures.